Affirming Moser's Well-Qualified Totus Christus. Issue 1 (February 2020) - Horton, Michael
David Moser argues that the " Totus Christus " motif is not only exegetically and theologically well-founded but important. This motif, associated especially with Augustine, has had a robust reception history to the present, but not primarily in Protestant, particularly evangelical, theologies. The concern expressed in my riposte is not with Moser's definition and defense of " Totus Christus, " which I find persuasive. Rather, I take exception to his description of my position in this paper, since I have defended " Totus Christus " with precisely the provisos that he recommends. Overall, however, I hope that David Moser's articulation of the motif receives a wide readership.